A novel model for calculating critical droplet entrainment rate of gas well considering droplet deformation and multiple parameters. Issue 6 (29th December 2020) - Xiao, Heng; Li, Xiao‐Ping; Tan, Xiao‐Hua; Li, Jinhan; Han, Chong; Xiao, Hang; Han, Zongzhi; Cao, Lina
Abstract: When a spherical droplet moves parallel to the direction of motion of its surrounding gas medium, it will deform into an ellipsoidal droplet. In this paper, an exposition of a novel model for predicting the minimum flow rate for the continuous removal of liquids from gas wells based on two theories is presented. First, droplet breakup principle is utilized to microscopically obtain the maximum size parameters of ellipsoidal droplets, and second, droplet force equilibrium is adopted to macroscopically calculate the critical droplet entrainment rate. Moreover, effect of variations in the windward area (attributed to droplet deformation) on the drag coefficient is determined. Impacts of variations in pressure, temperature, and pipe diameter on the gas‐liquid two‐phase friction resistance and gas‐liquid surface tension are also considered. For model verification and comparison with other droplet entrainment models, field data from 3436 gas wells are utilized. The field data well validates the results with a 92% accuracy, indicating that the new model has a better comprehensive performance in determining whether or not a gas well is loaded. Besides, parameter sensitivity analyses including the effects of drag coefficient, surface tension, and friction coefficient on the minimum flow rate of gas are performed. Finally, the relationship curve of critical droplet entrainment rates corresponding to different pressures and pipe diameters is established. Abstract : An optimization method for designing the manifold to obtain the uniform flow for each branch is proposed. The proposed model is validated under the turbulence condition. The effect of the static pressure change coefficient, local loss, and frictional loss on the accuracy of the model is studied.